The study of improving the compatibility of the blend of TVVM resin and polyester as a non-reactive hot melt adhesive used in OMD technique. Issue 18 (17th September 2019) - Song, Panke; Long, Jun; Bai, Yongping; Zhang, Chun; Cheng, Baoqiang
Abstract: Out-side mold decoration (OMD) is a new decoration technique for improving the surface quality and achieving colorful cosmetic surface of objects. In this paper, a non-reactive hot melt adhesive used in OMD technique was prepared from polyester (PES) and a terpolymer of vinyl choride-vinyl acetat-maleic anhydride (TVVM). For improving the compatibility of the two polymers, a bifunctional monomer (EHPA) with two different functional groups, –NH2 and –OH was synthesized in laboratory. Then a series of hot melt adhesives (PES-g-TVVM/EHPA) with different weight percentage of PES, TVVM/EHPA and Diphenyl-methane-diisocyanate (MDI) were obtained. The thermodynamic properties, softening point, cloud point, peeling strength and morphological characterization of the samples were tested for investigating the compatibility of components in HMAs. Finally, the OMD transfer films fabricated by using PES-g-TVVM/EHPA as bonding material were prepared for decorating plastic product, and the adhesion, acid and alkali resistance, impact resistance and heat resistance of the product surface were tested.